The Strategy of Private Forest Development in Bandar Dalam Village Sidomulyo District South Lampung Regency - Butar, Victor Butar; Duryat, Duryat; Hilmanto, Rudi (Jurnal Sylva Lestari, 2019)
The community forest is an alternative solution to the problem of the pressure of forest resources. The benefits obtained by the community depend on the management carried out by community forest farmers. This study aims to see and analyse the strategy of developing community forests in Bandar Dalam Village. The study was conducted in May 2015. The data collected is the potential data of wood analysed quantitatively. Measurement of wood potential data was carried out using a 10m x 10m square measuring plot with a sampling intensity of 1.3%. Analysis of Strengths, Weaknesses, Opportunities, and Threats was carried out to determine the right development in the community forests of Bandar Dalam Village. The community forest development strategy that needs to be implemented is the maintenance of trees, reducing the weakness of knowledge about forests by increasing knowledge about the benefits of forests and reducing threats by using simple technologies such as the use of complete agricultural tools and fertilisation. Keywords: forest products, wood private forests, the development strategy